The ASEAN Economic Community and Beyond. - Das, Sanchita Basu. (ISEAS - Yusof Ishak Institute, 2015)
The year 2015 has special significance for regional economic integration. The ASEAN Community, integrating the political, economic and social aspects of regional cooperation, will complete its first milestone by December 2015. Expectations of tangible benefits under an ASEAN Economic Community have attracted much attention though many of the initiatives will be realized post-2015. Following the policy of open regionalism, ASEAN has also signed free trade agreements with Australia, New Zealand, China, India, Japan and South Korea. It has launched negotiations for the Regional Comprehensive Econ.